THE INFLUENCE OF COLLABORATIVE CULTURE ON WORK-LIFE BALANCE WITH KNOWLEDGE MANAGEMENT CAPABILITY AS A MEDIATING VARIABLE AMONG POLICE OFFICERS - Dermawan, Arief; Abdillah, Muhammad Rasyid; Seswandi, Agus (Jurnal Daya Saing, 2026)
Police organizations operate in high-risk, time-pressured environments that demand constant vigilance, professionalism, and rapid response to unpredictable situations. Such conditions make maintaining work-life balance challenging, especially due to long hours, shift systems, and exposure to critical incidents, which may lead to stress and burnout. This study examines the effect of collaborative culture on work-life balance, with knowledge management capability as a mediating variable among police officers. Using a quantitative approach with PLS-SEM, data were collected through questionnaires and analyzed to assess direct and indirect relationships. The findings reveal that collaborative culture positively influences both knowledge management capability and work-life balance. Knowledge management capability also significantly affects work-life balance and partially mediates the relationship. These results highlight the importance of fostering collaboration and systematic knowledge sharing to enhance officers’ well-being and organizational effectiveness.